Vaccine adverse effects of children hospitalized during 1999 -2009 - Skawiński, Dariusz; Dutkiewicz, Sławomir; Marian Patrzałek, Marian (Polish Journal of Public Health, 2013)
Introduction. Protective vaccines are linked with the risk of Adverse Events Following Vaccinations (AEFV). In 1991, WHO introduced AEFV supervision. Aim. The aim of the work was the epidemiological analysis of the medical documentation of all hospitalized children in the Kielce Voivodeship Children’s Hospital with diagnosed AEFV. Material and methods. The documentation of 29 children who received polyvalent vaccinations and were hospitalized due to AEFV from 1999 to 2009 was analyzed and the results were statistically analyzed. Results. Medical records of 29 patients hospitalized with a diagnosis of AEFV. It was found that 64 of the vaccine may be the cause of AEFV: 19 were against Polio; 18 followed diphtheria, tetanus, and whole-cell pertussis vaccine (DTP); 10 after Haemophilus influenzae type B; five following each, INFANRIX hexa and DTaP and pneumococcus, hepatitis B virus, rotavirus and measles vaccines. These were second and third doses according to the sequence of administration. It was the following types of AEFV: hypotonic-hyporeactive episode (HHE) and continuous crying in seven, febrile convulsions in six, non-febrile convulsions in four. Seven children presented co-existing diseases after vaccination (pneumonia in two, pharyngitis in two, urinary tract infection in two, and viral gastroenteritis in one child). Recuperation allowed further vaccination. Conclusions. Polio, DTaP, and Hib vaccines most frequently caused AEFV (HHE, continuous crying, and febrile convulsions). A positive correlation between the number of vaccine components and AEFV frequency was not evident. All children with AEFV were cured without temporary or permanent disqualification from continued vaccinations, while a less reactogenic DTaP vaccine was recommended. We encourage registration of AEFV, even when patients do not require hospitalization